Morphing structures - Tan, Sharon Si Ying. (2009)
This project aims to investigate specific applications of smart materials in the design of a morphing wing. Smart materials have great potential in many fields, and are already widely used in some fields. This report will focus on application of smart materials, namely Smart Memory Polymer (SMP) and Smart Memory Alloy (SMA) in the area of morphing wings.